SAFE AND EFFECTIVE NURSING CARE: ASSESSMENT OF SURGICAL RISKS IN PERIOPERATIVE CARE OF ELDERLY PATIENTS - Melissa Orlandi Honório Locks; Darla Lusia Ropelato Fernandez; Lúcia Nazareth Amante; Karina Silveira de Almeida Hammerschmidt; Luciara Fabiane Sebold; Juliana Balbinot Reis Girondi (Universidade Federal do Paraná, 2016)
The present study aimed to examine the use of scales for assessment of surgical risks for elderly patients in the perioperative period. It involves a critical analysis of the principles of patient safety and care provided to elderly individuals undergoing surgical procedures, since nurses perform a comprehensive assessment in order to identify risk factors and prevent surgical complications. Search of scientific literature was performed in July and August 2015. The results obtained indicated that scales for predicting risks are patient care technologies that should be used by nurses in the perioperative period, in order to ensure a safe surgery. It is concluded that these scales can be used in the daily practice of nurses, through the establishment of an individualized care plan. Nursing should use this approach and contribute to the production of knowledge under this perspective, in order to implement interventions based on scientific evidence.